Genetic features of bovine viral diarrhea virus subgenotype 1c in newborn calves at nucleotide and synonymous codon usages - Wang, Huihui; Wang, Mengzhu; Feng, Xili; Li, Yicong; Zhang, Derong; Cheng, Yan; Liu, Junlin; Wang, Xiezhong; Zhang, Licheng; La, Hua; You, Xiaoqian; Ma, Zhongren; et al. (Frontiers in Veterinary Science, 2022)
Bovine viral diarrhea virus (BVDV), serving as an important pathogen for newborn calves, poses threat to reproductive and economic losses in the cattle industry. To survey the infection rate and genetic diversity of BVDV in newborn calves in northern China, a total of 676 serum samples of newborn calves were collected from four provinces between 2021 and 2022. All serum samples were individually detected for BVDV infection by RT-PCR and ELISA. Our results showed that the overall serological rate was 9.76 (66/676) and the average positive rate of BVDV RNA was 8.14% (55/676) in the newborn calves. Eight BVDV strains were successfully isolated from RT-PCR positive serum samples, and four isolates displayed the cytopathic effect (CPE). Based on phylogenetic tree at the genome level, the eight strains were classified into subgenotype1c. Moreover, the BVDV isolates had a close genetic relationship with the GSTZ strain at either nucleotide or codon usage level. Interestingly, in comparison of synonymous codon usage patterns between the BVDV isolates with CPE and ones without CPE, there were four synonymous codons (UCG, CCC, GCA and AAC) which displayed the significant differences (p values < 0.05) at codon usage pattern, suggesting that synonymous codon usage bias might play a role in BVDV-1c biotypes. In addition, the usage of synonymous codons containing CpG dinucleotides was suppressed by the BVDV-1c isolates, reflecting one of strategies of immune evasion of BVDV to its host. Taken together, our study provided data for monitoring and vaccination strategies of BVDV for newborn calves in northern China.